ВИХОВАННЯ ЗДОРОВОГО СПОСОБУ ЖИТТЯ ЯК ВАЖЛИВА УМОВА ГАРМОНІЙНОГО СТАНОВЛЕННЯ ОСОБИСТОСТІ (Pedagogy of Higher and Secondary Education, 2012)
У статті обґрунтовано проблему виховання здорового способу життя дітей та молоді як важливої умови гармонійного становлення особистості. Визначено вплив педагогічного доробку вчених в окреслену проблему; проаналізовано місце та роль виховних інституцій цього процесу; охарактеризовано фактори здоров’я. Ключові слова: виховання, здоровий спосіб життя, гармонійне становлення особистості, виховні інституції, фактори здоров’я.The problem of the education of healthy way of children and young people's lives as an important condition for harmonious becoming of a personality is grounded in the article. The influence of pedagogical works of scientists concerning the marked problem is determined; the importance and role of educational institutions in this process are analysed; the factors effecting health are characterized. Key words: education, healthy way of life, harmonious becoming of a personality, educational institutions, factors effecting health.
Keywords: education; healthy way of life; harmonious becoming of a personality; educational institutions; factors effecting health